Assessment of vegetation cover of three Araltobe islands using gis technologies (Journal of Geography and Environmental Management, 2023)
The article is devoted to the evaluation of the results obtained during field work using GIS technologies in the inventory of flora and analysis of the current state of vegetation on the example of the three islands of Araltobe.In 1968, in order to preserve the unique colony of the relict seagull, a nature reserve was created on three islands of Lake Alakol, but despite active efforts to protect the environment, the study of soils and vegetation of the territory is not carried out. Currently, the Araltobe Islands are a place that attracts tourists, so the protection of vegetation and wildlife is very important.The purpose of the work was to obtain objective, complete data on the state of vegetation cover, inventory, analysis and creation of a vegetation map of the Araltobe Islands using GIS technologies.In this regard, from 2016 to 2020, during field work based on the route-reconnaissance method, authors studied the flora for the first time and carried out their inventory of the three islands of Araltobe. All observations were carried out annually, during the flowering and fruiting period of the evaluated plant species.Two sites for observing plants were selected, a herbarium was collected and described. According to these studies, new plant species have been registered for the reserve. As a result of all the analyses and evaluation, a vegetation map of Araltobe was created using GIS.
Keywords: Alakol, Araltobe, vegetation cover, flora inventory, GIS, vegetation map.